Branch duct-type intraductal papillary mucinous neoplasm presenting as paraneoplastic small plaque para-psoriasis - Cyriac A Philips; Philip Augustine; Lijesh Kumar; George Joseph; Pushpa Mahadevan (Wolters Kluwer Medknow Publications, 2018)
To present and discuss a novel association between branch duct-type intraductal papillary mucinous neoplasm and paraneoplastic parapsoriasis. We present the case of a middle-aged male presenting with skin lesions that were suggestive of parapsoriasis, resistant to treatment, and in whom a diagnosis of branch-type intraductal papillary mucinous neoplasm of the pancreas was eventually made. A curative Whipple's surgery led to complete resolution of the skin lesions within 3 weeks. Paraneoplastic parapsoriasis in association with intraductal papillary mucinous pancreatic neoplasm has never been reported before.